Penerapan Permainan KarNuSik (Kartu Numerasi Asik) dalam Pembelajaran Matematika - Wardani, Putri Kusuma (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to evaluate the effectiveness of implementing the KarNuSik game (Kartu Numerasi Asik) in enhancing mathematical understanding and learning motivation among fifth-grade students at SD Negeri 58 Palembang. The research method employed is an experimental design using pre-test and post-test. The respondents of this study are 30 students who face difficulties in mathematics learning. Data were collected through pre-tests, post-tests, questionnaires, and observation sheets. The results indicate that the average pre-test score of the students was 65, while the average post-test score increased to 82, with a t-test showing a p-value < 0.05, indicating a significant difference. Furthermore, questionnaire analysis revealed that approximately 85% of the students reported an increase in their learning motivation after participating in the game. These findings suggest that the KarNuSik game not only enhances students’ understanding of mathematical concepts but also motivates them to participate more actively in learning. The social interactions that occur during the game also contribute to the development of students’ communication and collaboration skills. Despite these positive outcomes, some students still encounter difficulties with certain concepts, highlighting the importance of providing additional support from teachers. This study is expected to contribute to the development of more innovative and effective teaching methods in the classroom.